PENGARUH PENERAPAN ANDRAGOGI, SELF- REGULATED LEARNING, DAN LITERASI MEMBACA TERHADAP PEMANFAATAN BLENDED LEARNING BERBASIS LMS PADA CALON GURU PENGGERAK REGULER DI PROVINSI NTT [THE EFFECT OF ANDRAGOGY APPLICATION, SELF-REGULATED LEARNING, AND READING LITERACY TO THE USE OF LMS- BASED BLENDED LEARNING ON CALON GURU PENGGERAK REGULAR OF THE NINTH BATCH IN NTT PROVINCE] - Dethan, Sipromia -; Yugopuspito, Pujianto (Universitas Pelita Harapan, 2025)
Research on the utilization of LMS-based blended learning and the implementation of andragogy in the Program Pendidikan Guru Penggerak (PPGP) program for Calon Guru Penggerak (CGP) remains limited, particularly in East Nusa Tenggara (NTT) Province. As of 2023, this program has graduated eight cohorts of Guru Penggerak. However, the failure rate has increased over the last three cohorts. This study aims to analyze the influence of andragogy implementation, self-regulated learning (SRL), and reading literacy on the utilization of LMS-based blended learning among the ninth cohort of regular CGP in NTT Province. This research involved 152 respondents from 13 districts and one municipality in NTT. The findings indicate that for the ninth cohort of regular CGP in NTT Province: (1) andragogy implementation significantly influences the utilization of LMS-based blended learning; (2) SRL does not have a significant effect on the utilization of LMS-based blended learning; (3) reading literacy has a significant effect on the utilization of LMS-based blended learning; and (4) collectively, andragogy implementation, SRL, and reading literacy influence the utilization of LMS-based blended learning. Abstrak Bahasa Indonesia Penelitian mengenai pemanfaatan blended learning berbasis LMS serta implementasi andragogi dalam Program Pendidikan Guru Penggerak (PPGP) bagi Calon Guru Penggerak (CGP) masih sangat terbatas, terutama di Provinsi Nusa Tenggara Timur (NTT). Hingga tahun 2023, program ini telah meluluskan delapan angkatan guru penggerak. Namun, dalam tiga angkatan terakhir, tingkat ketidaklulusan mengalami peningkatan. Penelitian ini bertujuan untuk menganalisis pengaruh penerapan andragogi, Self-Regulated Learning (SRL), dan literasi membaca terhadap pemanfaatan blended learning berbasis LMS pada CGP reguler angkatan kesembilan di Provinsi NTT. Penelitian ini melibatkan 152 responden yang tersebar di 13 kabupaten dan satu kotamadya di Provinsi NTT. Hasil penelitian menunjukkan bahwa pada CGP reguler angkatan kesembilan di Provinsi NTT: (1) penerapan andragogi berpengaruh terhadap pemanfaatan blended learning berbasis LMS; (2) SRL tidak berpengaruh signifikan terhadap pemanfaatan blended learning berbasis LMS; (3) literasi membaca berpengaruh terhadap pemanfaatan blended learning berbasis LMS; dan (4) secara simultan, penerapan andragogi, SRL, dan literasi membaca berpengaruh terhadap pemanfaatan blended learning berbasis LMS.